Immunoproteomic identification of bovine pericardium xenoantigens - Griffiths, Leigh G., author; Orton, E. Christopher, advisor; Reardon, Kenneth F., advisor (Colorado State University. Libraries, 2008)
Bovine pericardium (BP) is an important biomaterial used in the production of gluteraldehyde-fixed heart valves and tissue engineering applications. The ability to perform proteomic analysis on BP is potentially useful for several reasons including investigation of immune rejection after implantation. The importance of humoral and cell mediated rejection responses towards such xenogeneic tissues are becoming increasingly apparent. I have applied a novel immunoproteomic approach to survey the antigenic determinants of BP. Proteomic analysis of fibrous tissues like BP is challenging due to their relative low cellularity and abundance of extracellular matrix. A variety of methods for tissue homogenization, protein extraction, and fractionation were investigated with the aim of producing high quality 2-DE gels for both water- and lipid-soluble BP proteins. MALDI-TOF/TOF MS protein identifications were performed to confirm bovine origin and appropriate subcellular fractionation of resolved proteins. Sixteen unique predominantly cytoplasmic bovine proteins were identified from the water-soluble gels. Twenty-two unique predominantly membrane bovine proteins were identified from the lipid-soluble gels. These results demonstrate that the final 2-DE protocol produced high quality proteomic data from BP for both cytoplasmic and membrane proteins. Duplicate 2-DE gels were used to generate western blots from both water- and lipid-soluble gels. Western blots were probed with pre- and post-exposure anti-BP rabbit serum, with detection of immune complexes limited to the IgG subtype. Western blots were compared to duplicate 2-DE gels and spots matched using Delta 2D image analysis software. Protein identifications of matched spots were performed using either MALDI-TOF/TOF MS or ESI MS/MS. This approach identified 31 putative antigens, capable of stimulating an IgG humoral rejection response. To the best of my knowledge, this study was the first to apply an immunoproteomic approach for identification of antigenic targets in xenotransplanted tissues. The results provide important information for understanding and possibly mitigating the immune response to fixed and unfixed BP xenografts.
Keywords: antigen; bovine pericardium; immunoproteomics; proteomics; tissue engineering; xenoantigens; animal sciences; animal diseases